PENGARUH PENGETAHUAN EKOLOGIS, KEMAUAN MEMBAYAR LEBIH, DAN KESADARAN LINGKUNGAN TERHADAP KEPUTUSAN KONSUMEN DALAM MEMBELI PRODUK ORGANIK - Diana Aqmala; Astrid Novianti (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2017)
Organic products as natural products or are free of chemicals /pesticides , is currently a trend in many countries around the world.The tendency of shifting consumer consumption patterns of consumingorganic products to conventional products has become an interestingphenomenon today . Shifting back to nature lifestyle , has become a wisechoice to meet a healthy lifestyle . This view , looking at the trend ofconsumers choosing organic ingredients and eco-friendly products isincreasing. Of the various existing studies , found that attention and thedesire to buy organic food and organic food products behavior isincreasing nowadays. The purpose of this study was to analyze theinfluence of ecological knowledge, willingness to pay more, andenvironmental awareness of the organic product purchase decisions inHortimart Agro Center Bawen .The population in this study is that consumers Hortimart AgroCenter Bawen. Based Slovin formula, the sample size was 100respondents were obtained with Purpose Sampling techniques , namelyconsumers who consume organic products . Primary data was collectedthrough questionnaires and analyzed using multiple linear.The resultsof the research on 100 respondents in Hortimart Agro EcologicalKnowledge Center showed that no significant influence on purchasingdecisions, different results are shown in the willingness to pay more andthe environmental awareness and significant positive influence onpurchasing decisions. willingnessto paymore variable (b2 =0,550)became the biggest factors influencing purchasing decisions.